Achievements and challenges in developing health leadership in South Africa: the experience of the Oliver Tambo Fellowship Programme 2008–2014. (8th July 2018) - Doherty, Jane; Gilson, Lucy; Shung-King, Maylene
Abstract: The Oliver Tambo Fellowship Programme is convened by the School of Public Health and Family Medicine, University of Cape Town, South Africa. It is a health leadership training programme with a post-graduate Diploma at its core, supplemented by management seminars, mentorship and alumni networking. An external evaluation was conducted in 2015 for the period since 2008. This rapid, descriptive study made use of mixed methods—including a document review of existing Programme material (management reports, anonymized alumni's implementation project reports, exit interviews, field interviews and e-mailed questionnaires), a brief e-mailed questionnaire, and 18 semi-structured telephonic interviews conducted by the evaluator with Programme alumni, convenors and senior government line managers. Data were analysed according to indicators and associated criteria developed by the evaluator on the basis of the Programme's objectives, international experience, the nature of the South African health system and the particular philosophy of the Programme. The evaluation found that the Diploma offered a unique contribution. This is because it sought less to convey new technical knowledge, than to empower and galvanize students to become change agents in the complex settings of their workplaces. Reflective practice was an important part of this process. Alumni were able to point to a number of positive changes in their management practice and motivation, translating these into improved performance by their teams and more effective health services. Alumni also helped to build the capacity of their own and other staff, sharing the knowledge and skills they had gained through the Programme, and leading by example. However, the Programme found it difficult to arrange adequate mentorship or peer support for alumni once they returned to their workplaces, pointing to the need for human resource development units in government to become more active in supporting alumni and holding them accountable for improving practice.